Intact CD100–CD72 Interaction Necessary for TCR-Induced T Cell Proliferation - Jiang, Xiaojun; Björkström, Niklas K.; Melum, Espen (Frontiers in Immunology, 2017)
Targeting CD100 by antibody blockade is a potential therapeutic strategy for cancers, but the functional effects on T cells following blockade of this immune activating molecule are rarely considered. Indeed, CD100 is highly expressed in T cells and anti-CD100 antibodies play a role during T cell proliferation, however, the outcome varies from different studies and the underlying mechanism is still unclear. To address this, monoclonal antibody clones directed against CD100 were evaluated. In their soluble form, four of these antibodies significantly reduced the expansion of T cells in the presence of bead-bound anti-CD3/CD28, either in total PBMC or purified T cell culture systems. Similar inhibition was seen when blocking CD100-CD72 interaction by soluble anti-CD72 instead of anti-CD100 antibodies. Conversely, restoring the interaction by CD72-Fc eliminated the soluble anti-CD100 induced inhibitory effect. Taken together, these results reveal that T cell proliferation is regulated by CD100 via interaction with CD72. They further establish an in vitro system to evaluate the inhibitory effect of anti-CD100 antibodies on T cells, to which attention should be paid in clinical trials in order to avoid potential side effects.